2022
DOI: 10.3390/ijms23073637
|View full text |Cite|
|
Sign up to set email alerts
|

Functional Characterization of the Solute Carrier LAT-1 (SLC7A5/SLC3A2) in Human Brain Capillary Endothelial Cells with Rapid UPLC-MS/MS Quantification of Intracellular Isotopically Labelled L-Leucine

Abstract: The solute carrier L-type amino acid transporter 1 (LAT-1/SLC7A5) is a viable target for drug delivery to the central nervous system (CNS) and tumors due to its high abundance at the blood–brain barrier and in tumor tissue. LAT-1 is only localized on the cell surface as a heterodimer with CD98, which is not required for transporter function. To support future CNS drug-delivery development based on LAT-1 targeting, we established an ultra-performance liquid chromatography–tandem mass spectrometry (UPLC-MS/MS) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…The existence of these advantages raised the intriguing question of whether using stable isotope labeled substrate as SLC substrate and LC-MS/MS as the detection method could develop an alternative to radioligand uptake assay for SLC. Although several uptake assays using stable isotope labeled substrates have been applied to study SLC functions, none has reported both the optimization of assay and the comparison to the radioactive method ( Gauthier-Coles et al, 2021 ; Bay et al, 2022 ; Papalazarou et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…The existence of these advantages raised the intriguing question of whether using stable isotope labeled substrate as SLC substrate and LC-MS/MS as the detection method could develop an alternative to radioligand uptake assay for SLC. Although several uptake assays using stable isotope labeled substrates have been applied to study SLC functions, none has reported both the optimization of assay and the comparison to the radioactive method ( Gauthier-Coles et al, 2021 ; Bay et al, 2022 ; Papalazarou et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, its expression is correlated with enhanced blood cell formation and metastasis. L-leucine was shown to switch on LAT-1 in cells and enable its uptake due to its high affinity for the transporter [65]. Moreover, a positive association of LAT1 with Ki67 and increased LAT1 expression with worse survival has been demonstrated [62].…”
Section: Slc Implication In Glioma Proliferation and Progressionmentioning
confidence: 99%
“…Other than FDA-recommended uptake transporters in the human brain, there are other uptake transporters essential for brain physiology [50]; LAT1(SLC 7A5/SLC2A3), which is responsible for the uptake of large neutral amino acids, thyroid hormones, and medicines, is one of them [51,52]. LAT1 is a light-chain amino acid uptake transporter connected by a disulfide bond to the heavy chain 4F2 cell-surface antigen heavy chain (4F2hc).…”
Section: Localization Functions and Expression Of The Drug Uptake Tra...mentioning
confidence: 99%